A humanisation approach for the management of Joint Hypermobility Syndrome/Ehlers-Danlos Syndrome-Hypermobility Type (JHS/EDS-HT). Issue 1 (1st January 2017) - Clark, Carol J.; Knight, Isobel
ABSTRACT: Joint Hypermobility Syndrome/Ehlers-Danlos Syndrome—Hypermobility Type (JHS/EDS-HT) is a complex and multisystemic condition which significantly impacts on a person's health and well-being and is challenging for health professionals (HPs) to manage. People with JHS/EDS-HT and HPs recognise the individual nature and the complexities of the condition. There is a requirement to understand the condition within the context of the individual human dimensions of illness and healing. The aim of this paper is to explore the management of this condition using a theoretical model referred to as the Humanisation Framework.  It is suggested that using the philosophical dimensions of this framework will empower HPs and those with JHS/EDS-HT to work together to proactively manage this condition. The eight dimensions of the Humanisation Framework facilitate an experiential understanding of the person within their context and environment, providing a constructive adjunct to the evidence-based management of those with JHS/EDS-HT. The humanisation framework was developed for health and social care and uses the philosophy behind well-being and what makes well-being possible. This paper explores how HPs may use aspects of the framework to understand the condition and empower and motivate those with JHS/EDS-HT to be active participants in their own well-being.